Digital Transformation in Government Procurement "A Comparative Analytical Study in Light of the Egyptian Legal System and Selected International Experiences" - Eltony, Waleed Mohamed (Social Empowerment Journal, 2025)
Government procurement is undergoing a profound transformation driven by global trends in digital governance. As a critical instrument for ensuring fiscal discipline, transparency, and fair competition, the digitalization of public tenders is increasingly recognized as a cornerstone of administrative reform. This study presents a comparative analytical assessment of the legal and institutional frameworks governing digital procurement, with a primary focus on the Egyptian experience. Drawing on international models—including those of Saudi Arabia, the United Arab Emirates, Bahrain, and South Korea—the research highlights the potential benefits of digital procurement, examines the main legal and technical obstacles, and proposes actionable recommendations to improve system performance. The study adopts a comparative analytical methodology that integrates theoretical foundations with practical insights, aiming to evaluate Egypt’s legal landscape in light of global standards of transparency, integrity, and good governance.